The psychometric properties of customer relationship management framework in the local government authorities in Zimbabwe - Douglas Chiguvi; Collen Mahambo (Dutch Journal of Finance and Management, 2020)
Although a lot of empirical studies have been conducted on customer-relationship-management (CRM), little research on the exploration of the psychometric properties of CRM scale items, in the Zimbabwean context has been conducted. This empirical study, based on key informant data drawn from sampled local government authorities in Zimbabwe (LGAZ), developed a reliable scale with demonstrated content and convergent validity. Amongst some of the reliable and valid antecedents and consequences of CRM Strategy success the study found; Due diligence, Strategy focus and alignment, Customer focus, Change management, Implementation Strategy, Implementation approach, Metrics, Project management, Process design, Buy-in and adoption to be some of the most important.. Therefore, using the confirmatory factor analysis approach, the research findings offer one more robustness in the applicability of CRM scale items by confirming that CRM city managers use psychometrically valid scale items to generate, disseminate and respond to information with a view to improving CRM performance of LGAZ.
Keywords: 650; psychometric properties of CRM; factor analysis approach; local government authorities; customer relationship management